Metformin attenuates fibroblast activation during pulmonary fibrosis by targeting S100A4 via AMPK-STAT3 axis - Ji, Huimin; Dong, Hongliang; Lan, Yuejiao; Bi, Yuqian; Gu, Xuan; Han, Yongyue; Yang, Chongyang; Cheng, Minghan; Gao, Jian (Frontiers in Pharmacology, 2023)
Fibroblasts activation is a crucial process for development of fibrosis during idiopathic pulmonary fibrosis (IPF) pathogenesis, and transforming growth factor (TGF)-β1 plays a key regulatory role in fibroblast activation. It has been reported that metformin (MET) alleviated bleomycin (BLM)-induced pulmonary fibrosis (PF) by regulating TGF-β1-induced fibroblasts activation, but the underlying mechanisms still deserve further investigations. In this study, MET blocked α-smooth muscle actin (α-SMA) accumulation in vivo accompanied with S100A4 expression and STAT3 phosphorylation inhibition, resulting in attenuating the progression of lung fibrosis after BLM administration. We determined that S100A4 plays critical roles in fibroblasts activation in vitro, evidenced by siRNA knockdown of S100A4 expression downregulated TGF-β1 induced α-SMA production in Human fetal lung fibroblast (HFL1) cells. Importantly, we found for the first time that the expression of S100A4 in fibroblasts was regulated by STAT3. Stattic, an effective small molecule inhibitor of STAT3 phosphorylation, reduced S100A4 level in TGF-β1- treated HFL1 cells accompanied with less α-SMA production. We further found that MET, which inhibits STAT3 phosphorylation by AMPK activation, also inhibit fibroblasts activation by targeting S100A4 in vitro. Together all these results, we conclude that S100A4 contributes to TGF-β1- induced pro-fibrogenic function in fibroblasts activation, and MET was able to protect against TGF-β1-induced fibroblasts activation and BLM-induced PF by down-regulating S100A4 expression through AMPK-STAT3 axis. These results provide a useful clue for a clinical strategy to prevent PF.